2018
DOI: 10.1155/2018/3034612
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Plants Used as Traditional Anticancer Remedies in Mkuranga and Same Districts, Tanzania, Using Brine Shrimp Toxicity Bioassay

Abstract: Background Inadequate specialized cancer hospitals and high costs are contributing factors that delay cancer patients from accessing health care services in Tanzania. Consequently, majority of patients are first seen by Traditional Health Practitioners (THPs) before they access specialized services. This study presents ethnomedical information and preliminary evaluation of 25 plant species claimed by THPs in Mkuranga and Same districts of Tanzania on use for treatment of cancer. Literature search and laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Most families encountered in this study have reported use in the traditional management of cancer in other countries across the globe. For example, Apocynaceae, Asteraceae, Bignoniaceae, Caricaceae, Fabaceae, Malvaceae, Meliaceae, Moraceae, Rutaceae, Sapindaceae, and Solanaceae were cited in Kenya [170], Ethiopia [238], Tanzania [97], and Near East (Arabian Peninsula, Egypt, Iraq, Iran, Israel, Jordan, Lebanon, Palestinian territories, Syria, and Turkey) [239], Lamiaceae in Morocco [240], and Apocynaceae, Meliaceae, and Malvaceae in Sri Lanka [241].…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
See 4 more Smart Citations
“…Most families encountered in this study have reported use in the traditional management of cancer in other countries across the globe. For example, Apocynaceae, Asteraceae, Bignoniaceae, Caricaceae, Fabaceae, Malvaceae, Meliaceae, Moraceae, Rutaceae, Sapindaceae, and Solanaceae were cited in Kenya [170], Ethiopia [238], Tanzania [97], and Near East (Arabian Peninsula, Egypt, Iraq, Iran, Israel, Jordan, Lebanon, Palestinian territories, Syria, and Turkey) [239], Lamiaceae in Morocco [240], and Apocynaceae, Meliaceae, and Malvaceae in Sri Lanka [241].…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
“…Zanthoxylum chalybeum Engl. is used in Ethiopia and Tanzania for the treatment of breast and cervical cancers [97,243], Blighia unijugata Baker is used for the treatment of breast and cervical cancers in Tanzania [97], while Cymbopogon citratus (DC.) Stapf is used against colorectal cancer in Kenya [170].…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
See 3 more Smart Citations